Role of central α1- and α2-adrenoceptors on the dipsogenic and cardiovascular effect of angiotensin II - Colombari, Eduardo [UNESP]; Saad, Wilson Abrão [UNESP]; De Arruda Camargo, Luiz Antonio [UNESP]; Renzi, Antonio [UNESP]; Luca Junior, Laurival Antonio de [UNESP]; Menani, José Vanderlei [UNESP] (Elsevier B.V., 1990)
We investigated the effects of previous central treatment with prazosin (an α1-adrenoceptor antagonist) or clonidine (an α2-adrenoceptor agonist) on the dipsogenic, pressor and tachycardic responses produced by intracerebroventricular (ICV) injection of angiotensin II (AII) in conscious rats. Holtzman rats with a chronic cannula implanted in the lateral ventricle were tested for dipsogenic and cardiovascular (arterial pressure and heart rate) responses in separate experiments. Previous ICV treatment with clonidine (20, 40, 80 and 120 nmol) abolished the pressor, tachycardic and dipsogenic effects of ICV AII. After all doses of prazosin (40, 80 and 120 nmol), AII induced bradycardic responses, but only the 80 and 120 nmol doses of prazosin reduced the pressor responses to AII. Prazosin produced no alteration in the dipsogenic effect of AII. The results show that the periventricular α1-adrenoceptors are involved only in the cardiovascular responses produced by central AII, whereas clonidine acting through α2-adrenergic and/or imidazole receptors can modulate all actions of AII. © 1990.
Keywords: α-Adrenoceptors; Angiotensin II; Arterial pressure; Thirst; Alpha 1 adrenergic receptor; Alpha 2 adrenergic receptor; Angiotensin; Clonidine; Prazosin; Animal experiment; Blood pressure; Heart rate; Intracerebroventricular drug administration; Male; Nonhuman; Priority journal; Rat; Thirst; Animal; Blood Pressure; Brain; Central Nervous System; Clonidine; Drinking Behavior; Heart Rate; Hemodynamics; Injections, Intraventricular; Male; Prazosin; Rats; Receptors, Adrenergic, alpha; Stereotaxic Techniques; Support, Non-U.S. Gov't; Animalia